Trends and patterns in Indian board structure - Soni, Tarun K; Arora, Akshita (Penerbit Universiti Kebangsaan Malaysia, 2021)
The board structure of Indian companies has witnessed a sea change in terms of its size and composition. Our study presents the trends and patterns in board characteristics for the last two decades for the top 500 companies listed on the Bombay Stock Exchange. We have made an attempt to measure variations across different sectors, age groups, and time periods in the mean values of variables by using one-way ANOVA. The differences between mean values and variances of board characteristics have been examined for two different time periods (2002-2010 and 2011-2019) using paired t-test. The contribution of our study is the comprehensive analysis of board trends suggesting significant differences in board size and composition across different sectors and time periods. The significant differences across different sectors also highlight heterogeneity among different sectors which should be taken into account while formulating different policies related to corporate governance. The regulatory reforms can be treated as crucial milestones towards developing stronger corporate governance mechanisms in India and regulators may deliberate on taking the reforms to the next level. Further, future scholars may ponder over the company’s strategic choices being followed for the functioning of their internal governance mechanism.